Determinants of Customers' Purchasing Intention of Fresh Agricultural Products: SEM Analysis - Dongrun Ma; Somjai Nupueng; Yan Chen; Zhenhua Xu (Emerging Science Journal, 2026)
With the ongoing advancement and widespread use of internet technologies, e-commerce has become a dominant retail channel, and the emergence of live-streaming platforms now offers companies a dynamic new way to market and sell products. Nevertheless, this business model also heightens the issue of information asymmetry, as consumers often face challenges in accurately assessing product quality and determining the credibility of sellers, making the enhancement of consumer trust a key concern for e-commerce enterprises. This study examines how information acquisition ability and online word of mouth regarding fresh agricultural products on Chinese live-streaming platforms influence consumers’ purchase intentions, with a particular focus on the mediating role of perceived value. Analysis of 372 valid survey responses reveals that both information acquisition ability and online word of mouth significantly increase purchase intentions, and that perceived value acts as a critical mechanism linking these factors. The findings also indicate the importance of real-time interaction in boosting sales and fostering deeper consumer engagement. Based on these insights, the study recommends strengthening consumers’ ability to access and evaluate product information, cultivating credible and positive online word of mouth, and leveraging interactive live-streaming features to enhance product displays and review systems. These contributions advance theoretical understanding of consumer behavior in digital marketing contexts and provide practical guidance for enterprises seeking to improve their live-streaming e-commerce strategies.